Hero's return - Daniels, B. J. (Daniels, B. J. Cahill Ranch novel., 2018)
Tucker Cahill disappeared from Gilt Edge, Montana, hoping to escape a secret that has haunted him for nineteen years. Then, when a young woman<U+2019>s remains are found in the creek near his family<U+2019>s ranch, he has no choice but to face his demons. The truth that sent him running years ago could take away his freedom now. Kate Rothschild came to town looking for vengeance<U+2014>and Tucker Cahill. What she finds is a tortured and irresistible man who<U+2019>s more than meets the eye. Caught up in the past, they are drawn deeper into a twisted game that<U+2019>s not over yet. And the consequences could prove fatal for them both<U+2026>